Integrated Effects of Safety Culture Dimensions on Occupational Health and Safety Performance: Insights from Balikpapan Refinery Contractors - Gultom, Dessy Chaterina Ullyma; Erislan, Erislan (Research Horizon, 2026)
The oil and gas sector faces high accident risks, making safety culture vital, especially for contractors. In Balikpapan’s refineries, gaps in perception, behavior, and support systems lead to inconsistent safety practices and lingering hazards. This study aims to examine the influence of safety culture dimensions, psychological, behavioral, and situational, on occupational health and safety performance among contractor workers in this high-risk setting. A quantitative approach was adopted using a cross-sectional survey of 382 contractor workers. Data were collected through a structured questionnaire with Likert-scale items and analyzed using partial least squares structural equation modeling. The measurement model confirmed validity and reliability after minor item refinement, while the structural model assessed direct and combined effects of the dimensions. Results show that all three dimensions positively and significantly influence occupational health and safety performance, with the situational dimension exerting the strongest effect, followed by behavioral and psychological dimensions. Together, the dimensions explained nearly seventy percent of the variance in performance. The study concludes that integrated development of organizational systems, consistent safe behaviors, and supportive worker perceptions is essential for enhancing safety outcomes in contractor-heavy environments. Strengthening situational factors offers the greatest potential for reducing risks and supporting zero-accident goals in the industry.